Utilização de resíduos de grãos de cervejaria na absorção do corante reativo azul 5G em soluções aquosas: sistemas batelada e leito fixo - Costa, Fabíola Melazo Amorim Silva (2020)
The textile sector is a major consumer of freshwater and its growing development results in the generation of large quantities of potentially toxic waste in watercourses, representing a serious threat to man and the environment. Biological treatment does not always present an effective solution for this type of effluent, leading to the need to use alternative treatment processes. Adsorption is an option that stands out due to its high efficiency and versatility, provided that a viable adsorbent is used for industrial application. This work aimed to study the adsorption of Reactive Blue 5G dye (RB5G), in a batch and fixed-bed system, using brewer spent grains (BSG) as an adsorbent. The adsorbent was characterized by particle size analysis, scanning electron microscopy, infrared spectroscopy, thermogravimetric analysis, and point of zero charge. A rotational central composite design (RCCD) was carried out in the study of batch adsorption and a complete factorial planning for the fixed bed, seeking to find conditions that could favor the dye adsorption process. The characterizations showed that BSG is a heterogeneous material, with an irregular surface and with the presence of pores, in addition to having functional groups on its surface that may be involved in the adsorption process. The adsorption kinetics was obtained, presenting an adsorption equilibrium time of approximately 24 h and a dye removal of 91.5%. Batch adsorption kinetics data were fitted to the pseudo- first-order and pseudo-second-order models, and the pseudo-second-order model was the one that best fitted the experimental data. The result of the statistical design performed for the batch system indicated that the dye adsorption capacity by the BSG was favored when the highest temperature values and lowest values of pH and mean particle diameter (MPD) were used. The adsorption isotherm was obtained under conditions capable of maximizing the result of adsorption capacity, and its data were adjusted to the Langmuir and Freundlich models. The Langmuir model was the one that best adjusted the isotherm data, reaching a maximum adsorption capacity of 83.42 mg g-1 . Considering fixed-bed adsorption, the statistical planning used showed that lower flow rates, associated with higher temperatures and adsorbent masses, resulted in a better performance of the adsorption column. The equilibrium data for the fixed bed were found and presented a good fit for both the Langmuir model and the Freundlich model, which may suggest the coexistence of chemical and physical adsorption. In general, the BSG showed good results for the adsorption of the dye RB5G, thus being an alternative for the removal of this dye.